PERANAN MEDIA GAGDET DALAM IMPLEMENTASI KEBIJAKAN PEMBELAJARAN PAI DI MASA PANDEMI COVID-19 - MOH. AINUR ROKHIM (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
The increasingly uncontrolled spread of Covid-19 led the government through the Minister of Education and Culture to issue S.E Number 4 of 2020 concerning the Implementation of Education Policies in an Emergency the Spread of Covid-19 which prohibits face-to-face learning in schools. Therefore, Learning must be done remotely or online by utilizing technology. This research is aimed at examining the challenges and roles of Gadget media in implementing Islamic Education learning policies during the Covid-19 pandemic. This research is a library research with descriptive-analytical literature methods and through conceptual and comparative approaches. The results of this study explain that gadget media has a very important role in implementing the Islamic Education Learning policy during the Covid-19 pandemic. Gadget media features and applications act as communication intermediaries and introductory students in stimulating attention, interests, thoughts, and feelings, enriching knowledge and experience, changing spiritual and social attitudes, and training their skills in Islamic Education Learning. Media gadgets make it easier for students to master spiritual, social, knowledge, and skills competencies in Islamic Education subjects without having to meet face to face. However, the use of gadget media besides having a positive side, it also has a negative impact on children's development. Therefore, the use of gadget media requires wisdom, intelligence, and parental involvement in educating, supervising, accompanying and instilling the principles of health, education, discipline, responsibility, and moral values ​​in children.